Rheology of bio-edible oils according to several rheological models and its potential as hydraulic fluid - Wan Nik, W. B.; Ani, Farid Nasir; Masjuki, H. H.; Eng Giap, S. G. (Elsevier B V, 2005)
Today's concern of protecting the environment has encouraged the research and the use of environmental friendly products. Bio-edible oils are potential energy transport media in hydraulic and lubricating systems. The use of bio-edible or vegetable oils as hydraulic fluid would help to minimize hazardous pollution caused by accidental spillage, lower disposal costs of the used fluid, and help the user industry to comply with environmental safety regulations. In order to successfully use these oils, an understanding of the oil properties is necessary in order to overcome the possible failures or obstacles that might occur in real operating conditions. Rheological property is one of the most important parameters and for this reason this parameter was investigated. The present work evaluates the temperature and shear rate effects of food grade oils that include palm, coconut, canola, corn and sunflower oils. A couette-type viscometer was used to determine the flow behavior of the oils at different temperatures and discrete shear rates that are ranged 40–100 °C and 3–100 rpm, respectively. Various empirical models such as Ostwald de-Waele, Cross, Carreau, Herschel–Bulkley and Arrhenius-type relationship were used to evaluate the experimental data. The influence of shear rate and temperature on the variation of viscosity was clearly observed but temperature has more significant influence. Interpretations of rheological models indicate that these food grade oils belong to pseudo-plastic category. The palm and sunflower oils are highly stable in terms of shear rate and temperature, respectively. The overall results suggest the potential substitution of food grade oils as an energy transport media.